2016
DOI: 10.1016/j.jbef.2016.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Clustering of annual general meetings and stock returns: UK evidence

Abstract: We find evidence of a significantly negative relationship between stock returns and the clustering of annual general meetings in the UK. The negative returns during the clustering of annual general meetings are not, however, economically significant. We caution against interpreting our results as evidence of a "new anomaly" in stock market returns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…The result holds for both interim and preliminary earnings announcements. Finally, while our study is related to the studies by Wang and Hefner (2014) and Lawal (2016), it differs from theirs as we examine the information content of AGMs but do not propose or test a stock return anomaly associated with AGMs.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The result holds for both interim and preliminary earnings announcements. Finally, while our study is related to the studies by Wang and Hefner (2014) and Lawal (2016), it differs from theirs as we examine the information content of AGMs but do not propose or test a stock return anomaly associated with AGMs.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 1 of this paper provides some evidence of monthly clustering of annual general meeting. Therefore, we include month fixed effects to account for the possible influence of clustering of AGMs on returns as reported by Lawal (2016) and Wang and Warner (2014). We find no evidence that the results presented in Table 5 are driven by clustering of annual general meetings.…”
Section: Changes In the Information Content Of Annual General Meetingsmentioning
confidence: 99%
“…The core business of AGMs traditionally and legally comprises three elements, summarized as legal formality, communication, and accountability (Apostolides, 2010). Studies that investigate an AGM assign different roles to it: a historical role (Jeacle, 2008), as a (an) corporate governance instrument, accountability, and transparency mechanism (Apostolides, 2010(Apostolides, , 2007Carrington and Johed, 2007;Cordery, 2005;Hodges et al, 2004;Strätling, 2003), and a powerful formal communication medium for the disclosure of financial information (Firth, 1981;Olibe, 2002;Garcia-Blandon et al, 2011Martinez-Blasco et al, 2014Lawal, 2016). By reviewing AGM studies in accounting, one finds out that most studies have assessed and analysed the impact of AGM announcements on capital market variables (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…By reviewing AGM studies in accounting, one finds out that most studies have assessed and analysed the impact of AGM announcements on capital market variables (e.g. Firth, 1981;Brickley, 1986;Rippington and Taffler, 1995;Olibe, 2002;Garcia-Blandon et al, 2011Martinez-Blasco et al, 2014Lawal, 2016), but there has been little consideration for the atmosphere at AGMs and the possible effects of their communications on shareholders' cognition and behaviour. Therefore, this study intended to investigate the effective elements of management communications in annual general meetings from the shareholder's viewpoint.…”
Section: Introductionmentioning
confidence: 99%
“…They specified that the applied method showed dissimilar performance in retrieving the economic information encoded in the Industrial Classification Benchmark and suggested that these dissimilarities would be connected to different degrees of sensitivity to the market mode dynamics [25]. Laval (2016) interestingly examined the relationship between frequency of annual general meetings and stock returns in UK and found a significantly negative relationship between stock returns and the monthly frequency of annual general meetings [21].…”
mentioning
confidence: 99%